The Integration of Restorative Justice in Indonesia’s Criminal Justice System: Building a Comprehensive Legal Framework - Johar, Olivia Anggie; Setiadi, Edi (Universitas Muhammadiyah Purwokerto, 2026)
The implementation of restorative justice in Indonesia has so far been fragmented, as each subsystem of the criminal justice system has issued its own regulations without comprehensive integration. This study examines the position of restorative justice within the Indonesian legal and criminal justice systems, while also proposing recommendations for its broader and more systematic application. Using a normative legal research method with statute and conceptual approaches, this study analyses secondary data through document review and literature study. The findings indicate that although restorative justice should, in principle, be applicable to all criminal offenses within the Indonesian legal system, its current application in the criminal justice system remains limited to specific cases. The novelty of this study lies in its proposal for an integrated legal framework—either through amendments to the Criminal Procedure Code (KUHAP) and the Criminal Code (KUHP) or through the enactment of a dedicated law—to comprehensively regulate restorative justice mechanisms. This contributes to the ongoing scholarly debate and provides a practical roadmap for legal reform in Indonesia.